2005
DOI: 10.1007/s00330-005-2647-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors: CT and MRI findings

Abstract: The objective of this study was to report the CT and MRI appearances of primary and metastatic gastrointestinal stromal tumor (GIST). The clinical and imaging findings of 31 patients with histological and immunohistochemical diagnosis of GIST were reviewed. The CT and MRI findings were assessed independently for size, location, enhancement characteristics, and pattern of metastatic disease. The tumors were of enteric (n=13), gastric (n=12), duodenal (n=2), and rectal (n=3) origin. In one case the primary site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
112
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(117 citation statements)
references
References 27 publications
3
112
1
1
Order By: Relevance
“…Many series do not present any case with this finding (3,22,29,30,32) , which is described in up to 2.5% of cases (16) . In our cases, we found one case presenting lymphadenopathy, with mitotic index lower than five mitosis per HPF.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Many series do not present any case with this finding (3,22,29,30,32) , which is described in up to 2.5% of cases (16) . In our cases, we found one case presenting lymphadenopathy, with mitotic index lower than five mitosis per HPF.…”
Section: Discussionmentioning
confidence: 92%
“…The disease is more common in the stomach and in individuals who are over 50 years old, with average age varying between 55 and 67 (29,31) . Clinical manifestations are unspecific and depend on the lesion site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case, the patient developed hemorrhagic shock; thus, upper endoscopy, colonoscopy, abdominal contrast-enhanced CT, and DBE were performed to investigate the source of the hemorrhage. Abdominal CT plays an important role in the diagnosis of small intestinal GISTs, particularly contrast-enhanced CT in cases with excessive bleeding (6,7). In the present case, abdominal contrast-enhanced CT revealed that the hemorrhagic source was the small intestine, although no tumor was detected.…”
Section: Discussionmentioning
confidence: 44%